Maintenance operation for open stadium / Mohamad Afdhal Rajuna - Rajuna, Mohamad Afdhal (Faculty of Architecture, Planning and Surveying, 2010)
Maintenance is the important thing for any building or space to make sure that the property asset is valuable in another year and so on. So the stadium is also requiring to have maintenance aspect to get the benefits as mention above. Through by a good management, it become more efficient for the stadium. This dissertation are to investigate on maintenance operation had been apply by stadium management and management of organization for three stadium . There are Stadium Merdeka, Stadium National Bukit Jalil, and Stadium Merdeka. Other than that, this dissertation will analyze on two types which for stadium staff and stadium occupant. The analyze will get the result by using questionnaire. It contain on Cleaning, complaint system, Damage on stadium elements, services, and electrical management, and problem at the stadium. Recommendation will be stated at Chapter 6 which refer from respondent result through by questionnaire. It can be take opportunity as improvement on stadium management.